O działaniu, zaniechaniu i dopuszczeniu śmierci - Marcin Ferdynus (Colloquia Theologica Ottoniana, 2013)
Categories of action, lack of action and release of death are the subject of lively discussion especially in the circle of analytic philosophy. Philosophical analysis in this article focuses essentially on the principle of symmetry and neo-Thomistic moral principles voluntarium indirectum because they play an important role in resolving the issue of moral dilemmas, or situations associated with a diffi cult choice between alternative options. The distinction between these three categories is crucial in matters related to the prolongation of human life and the release of death. Competing concepts, illustrating the analysis of the category of action, lack of action and the release of death, refer to the ideas of such thinkers as M. Tooley, D. Callahan, Ph. Foot, B. Williams, F.M. Kamm, B. Chyrowicz.